Hubungan Penggunaan Gadget dengan Interaksi Sosial Anak Usia Dini di Kelurahan Pasir Panjang Kecamatan Kota Lama Kupang - Maria Ariyanti Serlan; Khotijah Irul; Beatriks Novianti Bunga (Haumeni Journal of Education, 2021)
The aim of this study was to determine whether there was a significant connection between gadgets usage with early childhood kids’ social interaction at Pasir Panjang Kota Lama Sub-Disctrict Kupang City. This study used a quantitative study with correlation study design. Result showed that there is a significant connection between gadgets usage (X) and social interaction (Y) with correlation number as much as 0,808. This means the higher usage of gadgets will resulted in lesser social interaction between the early childhood kids and their environment. We recommend the parents to control the children’s playtime with their gadgets and spend more time to play with the kids as well as letting them to play with other kids.